Is organic farming environmentally friendly in North Europe? - Valkama, Elena; Perego, Alessia; Acutis, Marco (My University, 2021)
In North-European agriculture there is a risk of nitrogen leaching and the losses of soil organic C. Organic farming is regarded as a valuable option to halt these negative trends. In this study, the soil C dynamic and the N leaching were simulated using a process-based model in a site of South Savo region (Finland), comparing the effect of conventional and organic cropping systems in crop and livestock farms. In the crop farm, a rotation was cereal-based; the livestock farm was characterized by cultivation of cereals and grass. In the crop farm, the loss of soil C ranged from -0.7 and -0.5 Mg ha-1 yr-1 under the conventional system, while organic resulted in a higher sequestration rate, i.e. from -120 to +55 kg ha-1 yr-1. Leaching was generally low, especially in the organic systems. In the livestock farms, the observed C losses was lower than in the crop farms. The organic system was not beneficial, neither for C sequestration, nor for leaching on the livestock farms. Simulations under future climate indicate a general worsening, with more resilience in the organic systems on crop farms.
Keywords: carbon cycle; crop cultivation; organic farms; ARMOSA model; leaching; nitrates; climate changes